2017
DOI: 10.1016/j.molp.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Ordered Actin Structures Remodeled by Arabidopsis ACTIN-DEPOLYMERIZING FACTOR5 Are Important for Pollen Germination and Pollen Tube Growth

Abstract: Dynamics of the actin cytoskeleton are essential for pollen germination and pollen tube growth. ACTIN-DEPOLYMERIZING FACTORs (ADFs) typically contribute to actin turnover by severing/depolymerizing actin filaments. Recently, we demonstrated that Arabidopsis subclass III ADFs (ADF5 and ADF9) evolved F-actin-bundling function from conserved F-actin-depolymerizing function. However, little is known about the physiological function, the evolutional significance, and the actin-bundling mechanism of these neofunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 93 publications
(137 reference statements)
1
44
0
Order By: Relevance
“…The actin cytoskeleton is a highly dynamic structure that enables rapid responses to intracellular signaling molecules and regulatory proteins (Staiger et al, 1997;Zhu et al, 2013). It has been demonstrated that dynamic actin cytoskeleton rearrangements are regulated by a pool of actin-binding proteins and phytohormones (Hussey et al, 2006;Lanza et al, 2012;Jia et al, 2013;Zhu et al, 2017). Additionally, proteomic studies have shown that cytoskeletal proteins are regulated by a variety of posttranslational modifications, including phosphorylation, S-glutathionylation, nitration, S-sulfhydration, and S-nitrosylation (Lam et al, 2010;Yemets et al, 2011).…”
Section: CMmentioning
confidence: 99%
“…The actin cytoskeleton is a highly dynamic structure that enables rapid responses to intracellular signaling molecules and regulatory proteins (Staiger et al, 1997;Zhu et al, 2013). It has been demonstrated that dynamic actin cytoskeleton rearrangements are regulated by a pool of actin-binding proteins and phytohormones (Hussey et al, 2006;Lanza et al, 2012;Jia et al, 2013;Zhu et al, 2017). Additionally, proteomic studies have shown that cytoskeletal proteins are regulated by a variety of posttranslational modifications, including phosphorylation, S-glutathionylation, nitration, S-sulfhydration, and S-nitrosylation (Lam et al, 2010;Yemets et al, 2011).…”
Section: CMmentioning
confidence: 99%
“…During pollen germination and pollen tube growth, AtADF5, but not AtADF9, makes an important impact in the formation, organization, and maintenance of actin bundles [30]. The loss-function mutant of pollen specifically expresses AtADF7 which significantly suppresses the pollen tube growth [31] and AtADF10 is a pollen-specific ADF, however, AtADF7 and AtADF10 show different spatial profiles, indicating their unique functions in the pollen tube for regulating actin dynamics [16].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of the actin cytoskeleton are precisely regulated by a group of actin binding proteins (ABPs) (Ren and Xiang., 2007;Li et al, 2015). Several studies have found that the mutation of some ABPs, such as FIMBRIN5 (FIM5) and ACTIN-DEPOLYMERIZING FACTOR5 (ADF5), causes abnormal actin filaments in pollen grains and impairs germination Zhu et al, 2017). Formin is a potent actin nucleator that stabilizes the formation of actin nuclei and induces the assembly of parallel actin filaments for the formation of actin bundles or cables (A) Representative time-lapse images (maximal projection of z sections of the whole cell) of actin filaments labeled with Lifeact-mEGFP during pollen germination.…”
Section: Introductionmentioning
confidence: 99%